KAJIAN BAHASA RUPA BUDAYA MESATUA BALI DALAM CERITA BERGAMBAR - I Gede Yudha Pratama (LPPM Institut Bisnis dan Teknologi Indonesia, 2021)
Reviving oral traditions in Mesatua Balinese Culture seems far less than the written and image tradition. Mesatua Bali was once known as a culture that is conveyed by verbal storytelling, now it seems that it will be more efficient and interesting if it is copied in the appearance of a pictorial story (cergam), and it will be more interesting if it is presented in digital media. Interestingly, pictorial stories (cergam) greatly influence children's interest in following Balinese Mesatua culture. The Nusantara Katur Community adapts the Mesatua Balinese culture into a pictorial story made with a visual appearance that can arouse children's imagination when they can see. reading, and hearing a series of story satua (fairy tales) contained in a series of pictorial stories (cergam). Researchers used descriptive research methods to describe the characteristics of shape, color and composition through the study of visual language theory, starting from the content of the wimba, the way of the wimba, and the inner and outer layouts, in the view of pictures and documentation of the pictorial story works of the Nusantara Katur Community. The collection of materials is done by technique data reduction and data preparation to the conclusions presentation process. This research provides results results of visual language very indispensable role in supporting the illustrated story stories (cergam) that are presented. In addition to displaying visual images that are able to captivate children, they must also be able to present the plot of a story that is also attractive to children, because it is through a story idea that visuals can be created that are able to attract children's reading interest in pictorial stories (cergam).